2003
DOI: 10.1063/1.1555267
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of defects in nitrogen-doped polycrystalline Cu2O thin films by crown-ether cyanide treatment

Abstract: Crown-ether cyanide treatment, which simply involves immersion in KCN solutions containing 18-crown-6 followed by rinse, is studied in relation to electrical and optical properties of nitrogen-doped, polycrystalline Cu2O thin films, and its effect is compared with that of hydrogen treatment. By the crown-ether cyanide treatment, the luminescence intensity due to the near-band-edge emission of Cu2O at around 680 nm is enhanced, and the hole density is increased from the order of 1016 to 1017 cm−3, analogous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Akimoto et al suggested using nitrogen-doped Cu 2 O films that the CN treatment increases the hole concentration in Cu 2 O by forming Cu-CN bonds, i.e. passivating these defects 11,17 . Thus, the passivation using the CN treatment can reduce the number of the trapped holes that may act as charge recombination centers, resulting in increase in the charge separation yield at the interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akimoto et al suggested using nitrogen-doped Cu 2 O films that the CN treatment increases the hole concentration in Cu 2 O by forming Cu-CN bonds, i.e. passivating these defects 11,17 . Thus, the passivation using the CN treatment can reduce the number of the trapped holes that may act as charge recombination centers, resulting in increase in the charge separation yield at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…The CN treatment of a polycrystalline silicon surface indicated that the trap density was significantly decreased, resulting in dark saturation current reduction, in addition to a lowering in the surface charge recombination centers 15,16 . Recently, Akimoto et al reported that CN treatment of nitrogen-doped Cu 2 O thin films raised the hole density due to passivating surface defect states 17 . If the number of trapped holes becomes less owing to surface passivation, the increase in charge separation yield at the Cu 2 O/electrolyte interface and thus in the photocurrent can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…This cyanide treatment process avoids contamination by K + ions due to a formation of inclusion compounds with 18-crown-6 molecules, which capture K + ions effectively. Thus, CN -ions themselves can easily react with Cu 2 O [8]. As has been reported previously, the electrical and optical properties of Cu 2 O can be significantly improved by cyanide treatment due to the passivation of donor-like defects and non-radiative recombination centers.…”
mentioning
confidence: 74%
“…As mentioned above, the cyanide treatment has an effect of defect passivation in Cu 2 O, and the passivation mechanism may be the termination of Cu-dangling bonds, which give rise to localized energy levels deep in the band-gap [8,9]. To discuss the effect of cyanide treatment on the I-V characteristics, relative band diagrams of n-ZnO and p-Cu 2 O, and heterostructure are shown in Figs.…”
Section: Current-voltage (I-v) Characteristics Of Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation